2020
DOI: 10.2174/1570159x17666191001145550
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Neuronal Diseases in Zebrafish in the Era of CRISPR

Abstract: Background: Danio rerio is a powerful experimental model for studies in genetics and development. Recently, CRISPR technology has been applied in this species to mimic various human diseases, including those affecting the nervous system. Zebrafish offer multiple experimental advantages: external embryogenesis, rapid development, transparent embryos, short life cycle, and basic neurobiological processes shared with humans. This animal model, together with the CRISPR system, emerging imaging technologies, and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 132 publications
(139 reference statements)
0
8
0
Order By: Relevance
“…Our initial study reported mock ERGs in mice, rats, and humans, but we did not compare their time-frequency characteristics. Furthermore, we explored whether D. rerio displays such activity, since is a powerful experimental model for biomedical studies, including those affecting the nervous system directly ( Espino-Saldaña et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our initial study reported mock ERGs in mice, rats, and humans, but we did not compare their time-frequency characteristics. Furthermore, we explored whether D. rerio displays such activity, since is a powerful experimental model for biomedical studies, including those affecting the nervous system directly ( Espino-Saldaña et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Embryos were lysed in lysis buffer containing Tris buffer pH 7.0 and EDTA pH 8. The crude extract was used as template to amplify the CRISPR-targeted region of the PHLPP1 gene ( Espino-Saldaña et al., 2020 ; Sorlien et al., 2018 ). Indels were visualized using the heteroduplex mobility assay (HMA) on 10% native PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Zebrafish genome shares a high degree of synteny with both lower and higher vertebrate (from teleost fish to human) genomes [7,8]. Its sequence is fully accessible [9], a condition shared by many other teleost fishes, e.g., Japanese fugu (Fugu rubripes), green-spotted pufferfish (Tetraodon nigroviridis), medaka (Oryzias latipes), or three-spined stickleback (Gasterosteus aculeatus).…”
Section: Introductionmentioning
confidence: 99%